2003
DOI: 10.1016/s0895-7061(02)03149-7
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial damage and angiogenesis in hypertensive patients: relationship to cardiovascular risk factors and risk factor management

Abstract: In hypertension, the processes of endothelial damage and angiogenesis are abnormal, and correlate with overall cardiovascular risk. Indices of endothelial damage and angiogenesis are beneficially changed by intensive cardiovascular risk factor management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
84
2
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(98 citation statements)
references
References 22 publications
7
84
2
4
Order By: Relevance
“…It has previously been shown that plasma VEGF was higher in hypertensive patients compared with controls (25,26) and that the VEGF levels correlated significantly with age, systolic and diastolic blood pressure, 10-year cardiovascular disease (CVD) risk, and CVD risk scores. Indices of endothelial damage and angiogenesis are beneficially changed by intensive cardiovascular risk factor management (26).…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown that plasma VEGF was higher in hypertensive patients compared with controls (25,26) and that the VEGF levels correlated significantly with age, systolic and diastolic blood pressure, 10-year cardiovascular disease (CVD) risk, and CVD risk scores. Indices of endothelial damage and angiogenesis are beneficially changed by intensive cardiovascular risk factor management (26).…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Endothelial dysfunction is common in patients with different cardiovascular risk factors, that is, diabetes mellitus, 3 hypercholesterolaemia, 4 hyperhomocysteinaemia 5 and hypertension. 6 Several factors have been proposed to explain endothelial dysfunction such as reduction of the activity and/ or expression of the endothelial nitric oxide synthase (eNOS) and/or increased vascular formation of oxygen-derived free radicals. 7 There is growing evidence that increased levels of the endogenous NO synthase inhibitor asymmetric dimethylarginine (ADMA) may contribute to endothelial dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…5 Moreover, abnormal indices of angiogenesis in hypertension are correlated with target organ damage 6 and cardiovascular outcome. 4,7,8 The elevated Ang levels in hypertension suggest the possibility of alterations in the whole vessel remodelling process. 24 Given that angiogenesis plays a pivotal role in cardiovascular remodelling that may alter the mechanical wall properties, we sought a correlation between arterial stiffening, as expressed by pwv, and Ang-1 and Ang-2 gene expression in peripheral monocytes in patients with essential hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…4 In particular, hypertensive patients exhibit higher levels of plasma angiopoietin-1 (Ang-1) and Ang-2, 5 which are correlated with target organ damage 6 and cardiovascular outcome. 4,7,8 Although Angs may exert a potent mitogenic effect and promote arterial remodelling, 9 the underlying pathophysiological mechanisms potentially linking angiogenesis with adverse outcome in hypertension are largely unclear.…”
Section: Introductionmentioning
confidence: 99%